The workforce engagement equation : a practitioner's guide to creating and sustaining high performance - Manion, Jamison Jay (Taylor & Francis, 2012)
The Workforce Engagement Equation is for the hands-on leaders engaged in the frontline of affecting change?those who bear the scars of past failed initiatives yet continue to persevere. Describing the science behind the "Art of Managing" process improvement, it will help you bridge the gap between strategy and tactics and allow you to take concrete action to control ongoing operations sustainably.